Aprovechamiento de los residuos biomásicos de tres variedades de banano (Cáscaras) en la obtención de alcohol etílico. - Asas Chimborazo, Cristian Stalin (2023)
This project seeks to promote the reduction of organic waste that affects the ecosystem in order to opt for bioenergy manufacturing that partially replaces these resources, so its main objective is to take advantage of the biomass residues of the banana peel (Musa sp.), in obtaining ethyl alcohol. And among its specific goals were the physical and chemical characterization of the raw material (peels), the best combination of biomass residues for the most effective method of distillation for the conversion of glucose to ethanol, and the reaction kinetics of agro-industrial processing. A systematic review was carried out based on the raw material (shell), alcoholic fermentation of ethanol through simple and fractional distillation, maceration as a method of softening the shell, to determine the percentage of chemical compounds that constitute the ethyl alcohol obtained and mathematical models that can be applied within the distillation process. The experimental part was carried out in the Research Laboratory of the State University of Bolívar. A design in factorial arrangement AxBxC (3x2x2) was used, with three repetitions, where the study factors were banana varieties with three levels (Barraganete, silk and Orito), degree of maturity with two levels (mature and past ripe), sulfuric acid concentration with two levels (1 and 2%). Simple and fractional distillation was applied, prior to a maceration process of 8 and 12 hours of banana peel, the distillation time was 120 minutes. Response variables were glucose, alcohol, and alcohol yield.